Lead with Hospitality : be human, emotionally connect, serve selflessly - Scott, Taylor, 1979- (Ascent Audio, 2021)
Speaker, consultant, and hospitality industry veteran Taylor Scott knows that the most effective leaders approach their roles with heart, emotionally connecting with their team members before attempting to manage them. In Lead with Hospitality, Scott draws from his two decades in leadership roles at respected hotels, resorts, and restaurants. He distills the principles of gracious hospitality, translating them into actionable leadership lessons which apply in any industry, such as: how making people feel welcome fosters loyalty and keeps workers engaged with an organization's purpose; how serving people with empathy and compassion sparks workers' highest productivity; how making people feel comfortable encourages exploration, curiosity, and discovery while inviting everyone to lean into their creativity; and how making people feel significant drives them to deliver their best work. He also shares specific, practical steps you can take to put these principles into action. Scott shows how to connect, serve, engage, coach, and inspire your peers, teams, and even your own leaders. Lead with Hospitality is a call to action to connect with people on a human level which ultimately inspires teams, organizations, and companies to go to the next level.